A comparative Analysis of the Applicability of Forensic Science in the Criminal Justice System of Pakistan and USA - Sajid Hussain; Azhar Humayun khan; Rozi Ali; Sanobar Zaib; Dr. Naima Saeed (Review Journal of Social Psychology & Social Works, 2024)
Forensic science plays a pivotal role in criminal justice systems worldwide, offering scientific methods to solve crimes and prosecute offenders. This study examines the comparative status, challenges, and advancements in forensic science in Pakistan and the United States. While Pakistan's forensic science struggles with limited resources, inadequate facilities and training gaps The U.S.A possesses advanced technology, extensive resources, integration with law enforcement and judicial systems. However, ethical issues, racial disparities, and high operational costs are the challenge for U.S . The research underscores the critical role of emerging technologies like DNA profiling, artificial intelligence and digital forensics in revolutionizing forensic practices. It further advocates for enhancing Pakistan's forensic system through increased funding, specialized training, and international collaboration while the U.S.A needs to address ethical concerns and foster equitable forensic practices. This comparative analysis offers valuable insights for strengthening global forensic science, improving justice delivery and promoting fairness in legal system.